Identification of Vibrio sp. Bacteria in Intensive and Traditional Ponds of Vannamei Shrimp (Litopenaeus vannamei) in Teluk Pambang Village, Bengkalis Regency - Gustina, Lenny; Feliatra, Feliatra; Nursyirwani, Nursyirwani; Widantari, Meilya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
The identification of Vibrio sp. bacteria in the water of intensive and traditional ponds for vannamei shrimp in Teluk Pambang Village was conducted from March to June 2023. The aim of this research was to calculate the quantity of Vibrio sp. bacteria, understand the morphological characteristics, and identify the various types of Vibrio sp. bacteria in the water of intensive and traditional ponds for vannamei shrimp. The sampling involved collecting water from 2 bottles each from intensive and traditional ponds. Subsequently, Vibrio isolation from the water was cultured on selective TCBS media through three dilution steps. The bacterial count was then determined. Further, bacterial cultures from different colonies were streaked on TSA media, followed by identification through a series of morphological observations and biochemical tests. The research results indicate that the presence of Vibrio bacteria in intensive ponds complies with the maximum threshold and quality standards for a favorable environment for both the pond and shrimp. However, for traditional ponds, there is an abundance of Vibrio bacteria exceeding the threshold, where the maximum limit or good quality standard for Vibrio in the environment and shrimp is 103 CFU/ml. The morphological characteristics found include a round shape, green and yellow color, and a flat edge with emerging elevations. Furthermore, infections of Vibrio hollisae, Vibrio anguillarum, and Vibrio damsela were identified in the water of intensive and traditional ponds for vannamei shrimp (Litopenaeus vannamei) in Teluk Pambang Village, Bengkalis Regency.